Desain dan Implementasi Service Oriented Architecture Pada Sistem Informasi Geografis Pemerintah Kabupaten Lombok Barat - Irwan Hadi; Ida Bagus Ketut Widiartha; I Wayan Agus Arimbawa (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2017)
â€œBadan Penanaman Modal dan Pelayanan Perizinan Terpadu (BPMP2T)â€ handles a centralized and integrated the investment and licensing services in West Lombok Regency. BPMP2T has publish 2.114 of permits in 2015, but there has been no media or system used to publish the information disclosure. To solves these problems, it needs a system that can give a visualization of the location where the license takes place on map and displaying informations about license. Therefor this research is about Geographic Information System (GIS) Licensing to support the needs. GIS Licensing System integrated with â€œSistem Pelayanan Perizinan Terpadu (SPPT)â€, it takes an architecture for integration between that systems. Therefore, Service Oriented Architecture (SOA) is used. Phases of system development using the waterfall method which is divided into five phases that is analysis, design, implementation, testing, and documentation. SIGP implemented on mobile applications and web applications by utilizing the service to run it functionality. Based on the test results, show that the system meets the functional requirements that have been set. The test results obtained proven that SIG Licensing and SPPT can be integrated with each other by utilizing the serice that have been built to run on SIGP functionality.